The katydid that was: the tananá, stridulation, Henry Walter Bates and Charles Darwin. Issue 1 (April 2014) - Bidau, Claudio J.
<x xml:space="preserve">Abstract</x> The Amazonian bush-cricket or katydid, Thliboscelus hypericifolius (Orthoptera: Tettigoniidae: Pseudophyllinae), called tananá by the natives was reported to have a song so beautiful that they were kept in cages for the pleasure of listening to the melodious sound. The interchange of letters between Henry Walter Bates and Charles Darwin regarding the tananá and the issue of stridulation in Orthoptera indicates how this mysterious insect, which seems to be very rare, contributed to the theory of sexual selection developed by Darwin.